Autoimmune Fibrotic Adverse Reactions in One-Year Treatment with Cabergoline for Women with Prolactinoma - Aycicek Dogan, Bercem; Arduc, Ayse; Muslum Tuna, Mazhar; Berker, Dilek; Demirci, Nilgun; Demirtas, Semra; Cicekcioglu, Hulya; Guler, Serdar (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2016)
Aim: Cabergoline is related to an elevated risk of fibrotic adverse reactions including cardiac valvular and pleuropulmonary fibrosis. We investigated pulmonary and cardiac valve fibrosis and immunological markers before and after 3 and 12 months of treatment with cabergoline in women with prolactinoma. Material-Methods: The study included thirty-two women with newly diagnosed prolactinoma and 28 healthy women. CAB cumulative dose was 7.8±5.5 mg after 3-month therapy, and 31±22 mg after 12-month follow-up. The risk of autoimmune adverse fibrotic reactions related to CAB treatment including cardiac valvulopathy and pulmonary fibrosis were assessed by a transthoracic echocardiography and pulmonary function tests, respectively. Immunological markers including Antistreptolysin O, Rheumatoid factor, Immunglobuline E, Antinuchlear antibody were also evaluated. Results: Before the start of CAB therapy, the total prevalence of trace grade of mitral, aortic, pulmonic, and tricuspid valve regurgitations were found as 34%, 3%, 6.3%, and 39 % respectively in women with prolactinoma. After improving of prolactin levels with CAB treatment, no change was found in the prevalence of the all valve regurgitations. There was no deterioration in pulmonary function tests. Rheumatoid factor was found higher in newly diagnosed women with prolactinoma than in healthy women (p=0.01), and this was improved by CAB therapy (p=0.005). Conclusion: The prospective study indicated that sufficient cabergoline doses for a period of one year treatment of prolactinoma were not found to be related to fibrotic adverse reactions including cardiac valvular and pulmonary fibrosis or increased levels of immunological marker, apart from rheumatoid factor. For the first time Rf was found higher in newly diagnosed women with prolactinoma and was improved after cabergoline therapy.
Keywords: Cabergoline treatment